The Impact of Residual Thrombosis on the Long-Term Outcome of Patients with Deep Venous Thrombosis Treated with Conventional Anticoagulation - Prandoni, Paolo; Lensing, Anthonie W. A.; Prins, Martin H.; Pesavento, Raffaele; Piccioli, Andrea; Sartori, Maria T.; Tormene, Daniela; Milan, Marta; Vedovetto, Valentina; Noventa, Franco; Villalta, Sabina; Harenberg, Job (Seminars in Thrombosis and Hemostasis, 2015)
The impact of residual vein thrombosis (RVT) on the long-term outcome of patients with deep vein thrombosis (DVT) is unknown. We assessed the incidence of recurrent venous thromboembolism (VTE), postthrombotic syndrome (PTS), arterial thrombotic events, and cancer in patients with DVT with and without RVT. For this purpose, we evaluated up to 3 years 869 consecutive patients with acute proximal DVT who had conventional anticoagulation. RVT, defined as ultrasound incompressibility of at least 4 mm in the common femoral and/or the popliteal vein after 3 months, was detected in 429 (49.4%) patients, and was more likely in males (adjusted odds ratio [OR], 1.82; 95% confidence interval [CI], 1.37–2.04), in patients with previous VTE (OR, 1.64; 95% CI, 1.06–2.54), and in those with extensive thrombosis (OR, 3.58; 95% CI, 2.19–5.86). During the 3-year follow-up, recurrent VTE developed in 84 (19.6%) patients with RVT and 43 (9.8%) patients without RVT (adjusted hazard ratio [HR], 2.03; 95% CI, 1.40–2.94); PTS in 225 (52.4%) and 118 (26.8%), respectively (HR, 2.34; 95% CI, 1.87–2.93); arterial thrombosis in 29 (6.7%) and 14 (3.2%), respectively (HR, 2.05; 95% CI, 1.08–3.88); and cancer in 21 (4.9%) and 8 (1.8%), respectively (HR, 3.09; 95% CI, 1.31–7.28). In conclusion, in patients treated with vitamin K antagonists for prevention of recurrent VTE, RVT doubles the risk of recurrent VTE, PTS, arterial thrombosis, and cancer. Males, patients with previous VTE, and those with extensive thrombosis are independent risk factors of RVT development. Studies addressing the impact of the novel direct anticoagulants on the development of RVT as well as the long-term complications of DVT are needed.
Keywords: deep venous thrombosis; residual thrombosis; ultrasonography; post-thrombotic syndrome; cancer; arterial thrombosis